2011
DOI: 10.1007/s00005-011-0157-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of Lung Adenocarcinoma Patient with Peptide-Pulsed Dendritic Cells: a Case Report

Abstract: Immunotherapy with ex vivo generated dendritic cells (DCs) is reported to be of low toxicity and of diverse effectiveness in cancer treatment. The synthetic antigens are frequently used for immunotherapy especially for patients with stable disease after prior treatment. We described the effect of peptide-loaded DCs-based immunotherapy on patient with recurrent surgically resected adenocarcinoma with bronchoalveolar feature with co-existing of Takayasu arteritis and chronic hepatitis B. In January 2010, 61-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…This result may be explained by the fact that our cells were maintained longer in the presence of dexamethasone as the treatment for 1 hour is related to an in vivo instability of these cells, 47 while treatment for 48 hours produced better results in terms of inhibiting IFN-γ production by effector lymphocytes than a 6-hour treatment. 48 This effect in down-regulating IFN-γ was also observed after injection of TolDCs generated here, favoring the hypothesis that action of these cells is mainly systemic, affecting immune responses in peripheral lymphoid organs, since they were transplanted before allergy induction. In fact, Floderer et al 26 demonstrated that the subcutaneous immunization of wild-type mice with DCs affects the cytokine microenvironment in the spleen, causing T-cell phenotype reprogramming.…”
Section: Discussionsupporting
confidence: 75%
“…This result may be explained by the fact that our cells were maintained longer in the presence of dexamethasone as the treatment for 1 hour is related to an in vivo instability of these cells, 47 while treatment for 48 hours produced better results in terms of inhibiting IFN-γ production by effector lymphocytes than a 6-hour treatment. 48 This effect in down-regulating IFN-γ was also observed after injection of TolDCs generated here, favoring the hypothesis that action of these cells is mainly systemic, affecting immune responses in peripheral lymphoid organs, since they were transplanted before allergy induction. In fact, Floderer et al 26 demonstrated that the subcutaneous immunization of wild-type mice with DCs affects the cytokine microenvironment in the spleen, causing T-cell phenotype reprogramming.…”
Section: Discussionsupporting
confidence: 75%
“…Studies showed that the B cell and CD8 þ T cell, CD3 þ and FOXP3 þ T cells infiltration were significantly relative with the prognostic value in lung adenocarcinoma [25,26]. Moreover, DCs was also reported to be contributed to the immunotherapy of patient with lung adenocarcinoma [27]. Our previous study also showed that IL33 repressed the progression of PA via the regulation on DCs.…”
Section: Discussionmentioning
confidence: 80%
“…When DC vaccines are administered either simultaneously with or sequentially in combination with other anticancer agents, they can induce synergistic antitumor activity while minimizing the toxicity to normal hematopoietic or other organs (47)(48)(49). There are several methods to load DCs with tumor antigens.…”
Section: Discussionmentioning
confidence: 99%